Can You Love More Than One Person at the Same Time? A Research Report - Jankowiak, William; Gerth, Helen (Anthropologica, 2022)
The contemporary U.S. American model of love is that it is essentially a dyadic bond between two and only two indi viduals. Out of this bond arises feelings of eroticism, passion, and companionship which somehow merge together to form a unified conceptual whole. Co-existing with this ideal is an alternative model that survives in the popular medium of films that holds out the possibility of simultaneously loving two people at the same time. Our study was designed to explore how individuals caught in a concurrent love bond experience and managed their relationship(s). Implications of our findings are discussed below.